Recent and Massive Expansion of the Mating-Type-Specific Region in the Smut Fungus Microbotryum - Whittle, Carrie A. (Genetics, 2015)
The presence of large genomic regions with suppressed recombination (SR) is a key shared property of some sex- and mating-type determining (mat) chromosomes identified to date in animals, plants, and fungi. Why such regions form and how they evolve remain central questions in evolutionary genetics. The smut fungus Microbotryum lychnis-dioicae is a basidiomycete fungus in which dimorphic mat chromosomes have been reported, but the size, age, and evolutionary dynamics of the SR region remains unresolved. To identify the SR region in M. lychnis-dioicae and to study its evolution, we sequenced 12 genomes (6 per mating type) of this species and identified the genomic contigs that show fixed sequence differences between the mating types. We report that the SR region spans more than half of the mat chromosome (>2.3 Mbp) and that it is of very recent origin (∼2 × 10(6) years) as the average sequence divergence between mating types was only 2% in the SR region. This contrasts with a much higher divergence in and around the mating-type determining pheromone receptor locus in the SR, suggesting a recent and massive expansion of the SR region. Our results comprise the first reported case of recent massive SR expansion documented in a basidiomycete fungus.